Simulation using Interruptions - Bartkevicius, S.; Sarkauskas, K.; Vilkauskas, A. (Elektronika ir Elektrotechnika, 2011)
Simulation of control systems with large amount of interacting objects requires a powerful computer, because traditionally systems with polling are used. The number of conditions to check on each step of simulations becomes so large, that models become unfunction-al. The new simulation technique, using program interruptions, which are organized by the model itself is proposed. Replace of polling by interruptions lets radically increase the speed of simulation and simplify the model structure. Ill. 6, bibl. 7 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.150